Optimal investment planning for distributed generation / Muhammad Haikal Uzir - Uzir, Muhammad Haikal (2017)
This study proposes an approach by using particle swarm optimization (PSO) in order to obtain an optimal investment planning from the perspective of a distribution company (DISCO) for distributed generation (DG). The proposed method is tested on a 8-bus system and the results show that the investment of DISCO and the cost of operation are at minimum.